2007
DOI: 10.1038/nm1694
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis reveals a new IL-17A–dependent pathway of dendritic cell fusion

Abstract: IL-17A is a T cell-specific cytokine that is involved in chronic inflammations, such as Mycobacterium infection, Crohn's disease, rheumatoid arthritis and multiple sclerosis. Mouse models have explained the molecular basis of IL-17A production and have shown that IL-17A has a positive effect not only on granuloma formation and neurodegeneration through unknown mechanisms, but also on bone resorption through Receptor activator of NF-kappaB ligand (RANKL) induction in osteoblasts. Langerhans cell histiocytosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
1
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 28 publications
10
158
1
13
Order By: Relevance
“…IL-17A induces the production of proinfl ammatory mediators, metalloproteases, and antimicrobial peptides ( 15 ). We also demonstrated that IL-17A promotes long-term survival of monocyte-derived DCs and their fusion into multinucleated giant cells ( 16,17 ). In vitro, the short DC life span was extended above 12 days by exposure of DCs to IL-17A, suggesting that IL-17A-treated DCs may contribute to the development of chronic infl ammation resulting from multiple DC-T-cell cross talks, in vivo.…”
Section: Rna Extraction and Microarraysmentioning
confidence: 54%
“…IL-17A induces the production of proinfl ammatory mediators, metalloproteases, and antimicrobial peptides ( 15 ). We also demonstrated that IL-17A promotes long-term survival of monocyte-derived DCs and their fusion into multinucleated giant cells ( 16,17 ). In vitro, the short DC life span was extended above 12 days by exposure of DCs to IL-17A, suggesting that IL-17A-treated DCs may contribute to the development of chronic infl ammation resulting from multiple DC-T-cell cross talks, in vivo.…”
Section: Rna Extraction and Microarraysmentioning
confidence: 54%
“…However, naive T cells from patients suffering from hyper-IgE syndrome lost the potential to differentiate into Th17 cells [12]. In human donors suffering from Langerhans cell (LC) histiocytosis, IL-17A was found in skin LC, CD3/CD28-activated T cells, and monocyte-derived DC (MoDC), but not in MoDC from healthy donors [13]. Murine OVA-pulsed CD4 1 T cells secreted IL-17A after stimulation with skin-derived DC [14].…”
Section: Introductionmentioning
confidence: 99%
“…E.g. Wegener granulomatosis (Abdulahad et al 2008), Langerhans histiocytosis (Coury et al 2008), and hypersensitivity pneumonitis (Joshi et al 2009;Simonian et al 2009) have been reported to be linked to IL-17. Pulmonary IL-17 producing γδ T cells have also been detected in response to bleomycin-induced tissue damage, a model for induced pulmonary fibrosis (Braun et al 2010).…”
Section: Sarcoidosis Pulmonary Fibrosis and Other Interstitial Lung mentioning
confidence: 99%